Answer:
–x² + 12x + 5
Step-by-step explanation:
x² + 3x
–2x² + 9x + 5
The sum of the above expression can be obtained as follow:
.... x² + 3x
+ –2x² + 9x + 5
¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯
–x² + 12x + 5
¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯¯
Thus, the sum of x² + 3x and –2x² + 9x + 5 is –x² + 12x + 5
Answer: the equation is y = - 3x + 14
Step-by-step explanation:
The equation of a straight line can be represented in the slope intercept form as
y = mx + c
Where
c represents the y intercept
m represents the slope of the straight line.
The slope of the given line is - 3 and it contains the point (4, 2)
To determine the y intercept, we would substitute m = - 3, x = 4 and
y = 2 into y = mx + c. It becomes
2 = - 3 × 4 + c
2 = - 12 + c
c = 12 + 2
c = 14
The equation becomes
y = - 3x + 14
Answer:
Step-by-step explanation:
Use Pythagoras’ theorem
square of hypotenuse = sum of squares of two other sides
let the missing side be d
30^2 = 20^2 + d^2
600 = 400 + d^2
d^2 = 200
d = square root of 200
d = 14.142 cm